Geopolitics: the philosophy of place and its impact on the strategic performance of the state Iran and Turkey (Employment and Comparison Foundations) - Suhad Ismail Khalil (Tikrit Journal For Political Science, 2022)
The interpretation of the movement of regional and international interactions and the establishment of new concepts positioning on the basis of roles and functions. And adopting a geopolitical approach in creating a position towards leaders and decision makers in analyzing and realizing the power of government and defining its nature and function by identifying its strengths and effectiveness and identifying and neutralizing factors, all this requires a contemporary perspective if it is difficult for strategists to overcome or develop by finding strategic alternatives, it is It is possible to define the role and function of government in the regional context and its task in moving regional interactions through the formation of perceptions and visions of decision-makers or leaders, the ideological model and the ideological system of decision-making based on (Turkey and Iran) became the basis for the analysis of geopolitical power, which is represented in one of its existing forms. Which leads to employment that ensures real and real effectiveness of the importance of the place in a way that supports the national strength.